A safe method of extracting DNA from Coccidioides immitis - Austin Burt; Deidre A. Carter; Gina L. Koenig; Thomas J. White; John W. Taylor (Fungal Genetics Reports, 1995)
Human-pathogenic fungi such as Coccidioides immitis and Histoplasma capsulatum must be handled in Biosafety level 3 containment facilities which make for a very awkward working environment (J.Y. Richmond and R.W. McKinney, eds. Biosafety in Microbiological and Biomedical Laboratories, 3rd ed. NIH, Washington). In this paper we describe a safe and convenient method of extracting DNA from such fungi in which the culture is killed by steaming, allowing removal from the containment facilities, as soon as possible. The method was first developed with the non-pathogen Neurospora crassa, has worked well for both C. immitis and H. capsulatum, and should be useful for extracting DNA from any pathogenic fungus.